A polymeric triple-layered tablet for stratified zero-order drug release - Moodley, Kovanya (My University, 2013)
Patient compliance is a major factor in achieving optimal therapeutic outcomes. Pill burden, due to multiple drug therapies, has a great detrimental impact on compliance of the patient. Dose-dependent side-effects, associated with peak-trough plasma fluctuations of drugs, also have a negative impact on patient compliance with drug therapy. It is under these circumstances that zero-order drug release kinetics proves to be ideal. This is due to the lack of peak-trough fluctuations that occur with zero-order drug release, thereby minimizing the side-effects of drug therapy. Furthermore, a drug delivery system that may deliver more than one drug at a time may be beneficial to alleviate the pill burden associated with chronic diseases or specific health conditions. Novel drug delivery systems have been developed that offer zero-order or linear drug release. Amongst such systems are multilayered tablets. However these systems generally offer the delivery of just one drug. The development of a delivery system that is able to deliver up to three drugs in a zero-order manner may prove to be significantly beneficial to greatly increase patient compliance and in turn therapeutic efficacy. The purpose of this study was to design a novel triple-layered tablet (TLT) matrix targeted at achieving stratified zero-order drug release. The central factor for the establishment of the TLT was the selection of ideal and novel polymers that are capable of acting as superior drug release matrices. Modified polyamide 6,10 (PA6,10) and salted-out poly(lactic-co-glycolic acid) (PLGA) were employed as the outer drug-carrier matrices whereas poly(ethylene oxide) (PEO) was used as the middle layer drug matrix. Specialized granulation techniques and direct compression were employed to prepare the TLT matrices. Diphenhydramine HCl, ranitidine HCl and promethazine were chosen as model drugs for the study due to their similar high aqueous solubilities (100mg/mL). Matrix hardness, gel strength, swelling/erosion characteristics, Fourier Transform Infrared spectroscopy, Differential Scanning Calorimetry and in vitro drug release analysis employing High Performance Liquid Chromatography were performed on the TLT matrices in order to determine the physicomechanical and physicochemical nature of the TLT matrices. Computational molecular modeling (CMM) was employed to characterize the formation and dissolution of the TLT matrices. A box-Behnken experimental design was employed that resulted in the generation of 17 design formulations for ultimate optimization. In vivo animal studies were performed in the Large White Pig model to assess drug release behavior of the TLT. Ultra Performance Liquid Chromatography was employed for plasma sample analysis. The PA 6,10 layer provided relatively linear and controlled drug release patterns with an undesirable burst release greater than 15%, which upon addition of sodium sulphate was greatly reduced. The addition of PEO to the salted-out PLGA layer greatly reduced the initial burst release that occurred when salted-out PLGA matrix was used alone. Desirable results were obtained from FTIR, hydration and swelling/erosion analysis. CMM elucidated the possible mechanism of zero-order release from respective layers. Upon completion of the Box-Behnken design analysis, an optimized TLT formulation was established according to the formulation responses selected namely the rate constants and correlation coefficients. The TLT displayed desirable near linear release of all three drugs simultaneously over 24 hours, with approximately 10%, 50% and 90% of the drugs released in 1, 10 and 24 hours. An in vitro drug release comparison performed between the optimized TLT and the commercial tablets currently used, showed an unequivocal display of superiority of the TLT in terms of linear drug release over commercial tablets. A cardiovascular related drug regimen (Adco-simvastatin®, DISPRIN CV® and Tenormin 50®) was applied to the TLT to assess the flexibility of incorporating a range of drugs. The TLT furthermore provided near linear to linear release of the therapeutic regimen over 24 hours and maintained superiority over the commercial tablets. Benchtop Magnetic Resonance Imaging, porosity analysis and Scanning Electron Microscopy was utilized for further introspective characterization of the TLT. In vivo analysis demonstrated a definite control of drug release from the TLT as compared to commercial tablets which further confirmed the advantage of the TLT.
Keywords: Drug Delivery Systems